The cytochrome P450 family in the parasitic nematode Haemonchus contortus. Issue 4 (March 2015) - Laing, Roz; Bartley, David J.; Morrison, Alison A.; Rezansoff, Andrew; Martinelli, Axel; Laing, Steven T.; Gilleard, John S.
Abstract : Graphical abstract: Highlights: The Haemonchus contortus genome encodes a large family of cytochrome P450 (CYP) genes. Haemonchus contortus lacks the dramatic CYP family expansions seen in Caenorhabditis elegans . Haemonchus contortus orthologues of C. elegans CYPs share similar expression profiles. The majority of H. contortus CYPs are most highly expressed in larval stages. The parasite intestine is a major site of CYP expression. Abstract: Haemonchus contortus, a highly pathogenic and economically important parasitic nematode of sheep, is particularly adept at developing resistance to the anthelmintic drugs used in its treatment and control. The basis of anthelmintic resistance is poorly understood for many commonly used drugs with most research being focused on mechanisms involving drug targets or drug efflux. Altered or increased drug metabolism is a possible mechanism that has yet to receive much attention despite the clear role of xenobiotic metabolism in pesticide resistance in insects. The cytochrome P450s (CYPs) are a large family of drug-metabolising enzymes present in almost all living organisms, but for many years thought to be absent from parasitic nematodes. In this paper, we describe the CYP sequences encoded in the H. contortus genome and compare their expression in different parasite life-stages, sexes and tissues. We developed a novel real-time PCR approach based on partially assembled CYP sequences "tags" and confirmed findings in the subsequent draft genome with RNA-seq. Constitutive expression was highest in larval stages for the majority of CYPs, although higher expression was detected in the adult male or female for a small subset of genes. Many CYPs were expressed in the worm intestine. A number of H. contortus genes share high identity with Caenorhabditis elegans CYPs and the similarity in their expression profiles supports their classification as putative orthologues. Notably, H. contortus appears to lack the dramatic CYP subfamily expansions seen in C. elegans and other species, which are typical of CYPs with exogenous roles. However, a small group of H. contortus genes cluster with the C. elegans CYP34 and CYP35 subfamilies and may represent candidate xenobiotic metabolising genes in the parasite.